An FPGA-Based Fully Synchronized Design of a Bilateral Filter for Real-Time Image Denoising - Gabiger-Rose, Anna; Kube, Matthias; Weigel, Robert; Rose, Richard (IEEE Transactions on Industrial Electronics, 2014)
In this paper, a detailed description of a synchronous field-programmable gate array implementation of a bilateral filter for image processing is given. The bilateral filter is chosen for one unique reason: It reduces noise while preserving details. The design is described on register-transfer level. The distinctive feature of our design concept consists of changing the clock domain in a manner that kernel-based processing is possible, which means the processing of the entire filter window at one pixel clock cycle. This feature of the kernel-based design is supported by the arrangement of the input data into groups so that the internal clock of the design is a multiple of the pixel clock given by a targeted system. Additionally, by the exploitation of the separability and the symmetry of one filter component, the complexity of the design is widely reduced. Combining these features, the bilateral filter is implemented as a highly parallelized pipeline structure with very economical and effective utilization of dedicated resources. Due to the modularity of the filter design, kernels of different sizes can be implemented with low effort using our design and given instructions for scaling. As the original form of the bilateral filter with no approximations or modifications is implemented, the resulting image quality depends on the chosen filter parameters only. Due to the quantization of the filter coefficients, only negligible quality loss is introduced.
elib2cris::1512001600,gabiger-rose2014
Keywords: Bilateral filter; field-programmable gate array (FPGA)

A Synchronous FPGA Design of a Bilateral Filter for Image Processing - Gabiger-Rose, Anna; Kube, Matthias; Weigel, Robert (35th Annual Conference of the IEEE Industrial Electronics Society, 2009)
elib2cris::1512001600,gabiger2009

Automatically Adjustable Real-Time Capable Noise Filtering in Image Processing - Gabiger-Rose, Anna; Kube, Matthias; Schmitt, Peter; Weigel, Robert (Embedded World, 2011)
In this work, a way to achieve the best noise suppression in images while preserving the spatial resolution is presented. The noise filtering is done by means of a bilateral filter. The denotation bilateral filtering suggests the combination of domain and range filtering. The domain filter averages the nearby pixel values and acts thereby as a low-pass filter. The range filter stands for the nonlinear component and plays an important part in edge preserving. Both filtering components can be adjusted by according parameters. In this work the way is presented, how the adjustment parameter for the nonlinear photometric component of the filter can be derived from the noise standard deviation, which allows the highest PSNR increase while retaining the structural similarity index at high level. The noise statistics is measured during the initialization of the camera and stored for the filtering purpose. Using the presented instruction for the calculation of the adjustment parameter of the photometric component an automatical adjustment of the noise filter is possible, whereas the adjustment can be done for any noise standard deviation. It is shown, that utilizing the instruction for the automatical adjustment of the noise filter the noise suppression without a loss of structural information is achievable at any noise level.
elib2cris::1512001600,gabiger-rose2011

Enhancement of CT Image Quality via Bilateral Filtering of Projections - Gabiger-Rose, Anna; Weigel, Robert; Oeckl, Steven; Schmitt, Peter (The First International Conference on Image Formation in X-Ray Computed Tomography, 2010)
In this paper, the way to enhance the image quality of 3D-CT reconstruction by means of noise filtering in 2D projections is shown. The noise reduction is done by applying a bilateral filter, which is well known for its edge-preserving quality. During the measurement of the projections the noise signal of the system is superimposed to the image signal. This noise propagates into the reconstruction and can be measured in the cross sections of the reconstructed volume. In order to reduce the noise in the volume, the preprocessing of the projections is extended by noise filtering prior to the logarithm transform and the ramp filtering. The capability of the bilateral filter to reduce image noise without blurring or corruption of the image contents combined with the real-time implementation on FPGA makes this filter suitable for the application to the x-ray projections. As it is shown in this paper, not only the noise is suppressed in the reconstruction, but due to the edge-preserving filtering of noise in the projections the structural details in the reconstruction are resolved better.
elib2cris::1512001600,gabiger2010

Image denoising using bilateral filter with noise-adaptive parameter tuning - Gabiger-Rose, Anna; Kube, Matthias; Schmitt, Peter; Weigel, Robert; Rose, Richard (IECON 2011 - 37th Annual Conference on IEEE Industrial Electronics Society, 2011)
In this work, a novel way to adjust a bilateral filter is presented. The bilateral filter is a combination of domain and range filtering. The domain filter acts as a low-pass filter. The range filter stands for the nonlinear component and plays an important part in edge preserving. Both filtering components can be adjusted by according parameters. Pursuant to our experience and achieved results in terms of the image quality it is more effective to readjust the range filter to the noise level than to cope with the fine tuning of the spatial filter. In this work, we show how the adjustment parameter for the nonlinear range component can be derived from the standard deviation of noise, which allows automatic noise-adaptive adjustment of the filter.
elib2cris::1512001600,gabiger-rose2011b

Noise-adaptive bilateral filtering of projections for Computed Tomography - Gabiger-Rose, Anna; Rose, Richard; Kube, Matthias; Schmitt, Peter; Weigel, Robert (11th International Meeting on Fully Three-Dimensional Image Reconstruction in Radiology and Nuclear Medicine, 2011)
In this work, the image quality enhancement of CT images via filtering of noise in the projections is shown. For denoising, a noise-adaptively adjustable bilateral filter is exerted. The application area of the presented work is nondestructive testing in the industry. Bilateral filtering incorporates the combination of domain and range filtering. The domain filter averages the nearby pixel values and acts thereby as a low-pass filter. The range filter stands for the nonlinear component and plays an important part in edge preserving. These filter components both can be adjusted by corresponding parameters. In this paper, the way is presented how the parameter for the adjustment of the nonlinear component can be derived from the standard deviation of noise. This approach allows to increase the PSNR_dB while retaining the structural similarity MSSIM at a high level. Using the proposed method for the calculation of the range filter parameter an automatic noise-adaptive tuning of the noise filter is possible. Moreover filter tuning is effective for any noise level. Besides the increase of the PSNR_dB and of the MSSIM it is demonstrated, that owing to the bilateral filtering of projections the detectability of the low contrast details in CT images can be improved. As long as the details can be distinguished from noise, it is possible to enhance the contrast resolution of these details due to the bilateral filtering of projections using our proposed filter adjustment.
elib2cris::1512001600,gabiger-rose2011a